Neuropeptide‐S‐receptor deficiency affects sex‐specific modulation of safety learning by pre‐exposure to electric stimuli. (2nd January 2020) - Kreutzmann, Judith C.; Khalil, Radwa; Köhler, Jana C.; Mayer, Dana; Florido, Antonio; Nadal, Roser; Andero, Raül; Fendt, Markus
Abstract: Neuropeptide S (NPS) is a neuropeptide involved in the regulation of fear. Because safety learning is impaired in patients suffering from anxiety‐related psychiatric disorders, and polymorphisms of the human neuropeptide S receptor (NPSR) gene have also been associated with anxiety disorders, we wanted to investigate whether NPSR‐deficiency interferes with safety learning, and how prior stress would affect this type of learning. We first investigated the effect of pre‐exposure to two different types of stressors (electric stimuli or immobilization) on safety learning in female and male C57Bl/6 mice, and found that while stress induced by electric stimuli enhanced safety learning in males, there were no differences in safety learning following immobilization stress. To further investigate the role of the NPS system in stress‐induced modulation of safety learning, we exposed NPSR‐deficient mice to stress induced by electric stimuli 10 days before safety learning. In nonstressed male mice, NPSR‐deficiency enhanced safety learning. As in male C57Bl/6 mice, pre‐exposure to electric stimuli increased safety learning in male NPSR +/+ mice. This pre‐exposure effect was blocked in NPSR‐deficient male mice showing impaired, but still intact, safety learning in comparison to their NPSR +/+ and NPSR +/− littermates. There was neither a pre‐exposure nor a genotype effect in female mice. Our findings provide evidence that pre‐exposure to stress induced by electric stimuli enhances safety learning in male mice, and that NPSR‐deficiency prevents the beneficial effect of stress exposure on safety learning. We propose an inverted U‐shape relationship between stress and safety learning. Abstract : Neuropeptide‐S deficiency prevents the beneficial effect of stress exposure on safety learning in male mice.